Finding the fifth intercostal space for chest drain insertion: guidelines and ultrasound. Issue 12 (5th October 2015) - Bowness, J S; Nicholls, K; Kilgour, P M; Ferris, J; Whiten, S; Parkin, I; Mooney, J; Driscoll, P
Abstract : Objectives: International guidelines exist for chest drain insertion and recommend identifying the fifth intercostal space or above, around the midaxillary line. In a recent study, applying these guidelines in cadavers risked insertion in the 6th intercostal space or below in 80% of cases. However, there are limitations of cadaveric studies and this investigation uses ultrasound to determine the intercostal space identified when applying these guidelines in healthy adult volunteers. Methods: On each side of the chest wall in 31 volunteers, the position for drain insertion was identified using the European Trauma Course method, Advanced Trauma Life Support (ATLS) method, British Thoracic Society's 'safe triangle' and the 'traditional' method of palpation. Ultrasound imaging was used to determine the relationship of the skin marks with the underlying intercostal spaces. Results: Five methods were assessed on 60 sides. In contrast to the cadaveric study, 94% of skin marks lay over a safe intercostal space. However, the range of intercostal spaces found spanned the second to the seventh space. In 44% of women, the inferior boundary of the 'safe triangle' and the ATLS guidelines located the sixth intercostal space or below. Conclusions: Current guidelines often identify a safe site for chest drain insertion, although the same site is not reproducibly found. In addition, women appear to be at risk of subdiaphragmatic drain insertion when the nipple is used to identify the fifth intercostal space. Real-time ultrasonography can be used to confirm the intercostal space during this procedure, although a safe guideline is still needed for circumstances in which ultrasound is not possible.